The Importance and Necessity of Psychological First Aid Competency Through the Observations and Experiences of Volunteer Librarians in the Earthquake Zone - Polat, Özgür (Information World, 2024)
It is possible for individuals to get out of the effects of psychological trauma, which occurs as a result of being negatively affected by the events they have experienced, and to regain normal conditions through planned methods. One of these methods is psychological first aid. The aim of this study is to reveal the importance of librarians having psychological first aid skills through the selected sample and to offer solutions by addressing the problems in this regard. The findings of the study are based on the evaluation of the observations and experiences of volunteer librarians who went to the earthquake zone and provided library services after the disaster centered in Kahramanmaraş on February 6, 2023. Within the scope of the research, a semi-structured questionnaire was used in face-to-face interviews with nine librarians. The data were analyzed using descriptive content analysis. The findings show that librarians provide both basic librarianship services and services in various themes depending on the expectations and needs of the people in the earthquake zone, children in the earthquake zone are more interested in games and recreational activities in the mobile library, and adults need people with whom they can share their feelings and thoughts. Based on the observations and experiences of librarians in the earthquake zone, the study concluded that librarians should receive psychological first aid training and improve their knowledge and skills in this area. As a result of the evaluation, it was suggested that librarians and expert psychologists should work together to create materials for library-based psychological first aid training. What makes this research unique and different from the studies on psychological first aid in the information science literature is that it was planned by putting librarians at the center and the results were obtained with an evidence-based approach based on the real experiences of librarians. It is thought that this research will fill an important gap in the national literature since there is no evidence-based scientific publication that deals with psychological first aid and librarians together.